Construction of diazepine-containing spiroindolines via annulation reaction of α-halogenated N-acylhydrazones and isatin-derived MBH carbonates - Liu, Xing; Shi, Wenjing; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2023)
A straightforward synthetic protocol for the efficient construction of diazepine-containing spiroindolines has been developed and proceeds through a by base-promoted annulation reaction of α-halogenated N-acylhydrazones and isatin-derived MBH carbonates. The reaction mechanism of this formal [4 + 3] annulation includes the in situ generated allylic ylide, nucleophilic substitution, Michael additon, and elimination processes. Additionally, the similar reaction with α-halogenated N-tosylhydrazones also afforded N-tosyl-substituted spiro[indoline-3,5'-[1,2]diazepine] in satisfactory yields. This protocol provides a convenient approach for the assembly of diverse highly functionalized spiro[indoline-3,5'-[1,2]diazepines] and also features a broad substrate scope, simple reaction conditions, and high molecular convergence.
Keywords: acylhydrazone; annulation; azepine; MBH carbonate; spirooxindole